Spectroscopic behavior of loratadine and desloratadine in different aqueous media conditions studied by means of TD-DFT calculations - Brasca, Romina (2013)
In this study, we explained the influence of the stepwise protonation of two antihistaminic drugs on their experimental absorption spectra. We demonstrated the capability of the TD-CAM-B3LYP method, combined with a polarizable continuum model, to produce good performance for the calculated spectra. The lowest energy transitions and the molecular orbital plots were analyzed in detail. The calculated UVspectra are proposed as potential alternatives to initialize the well-known-MCR-ALS algorithm, especially when the spectra of the pure analytes are not available. Moreover, it can be a useful strategy for planning an experimental methodology oriented to multiway analysis when the drug species exhibit acid-base properties.